ANALYSIS OF ELIGIBILITY AND USEFULNESS BIOLOGY STUDENTS’ WORKSHEET ON BIOLOGICAL TECHNOLOGY INNOVATION TOPIC IN CLASS X - Bintang, Syahana Sabila Fajriah (Jurnal Pelita Pendidikan, 2024)
This study aims to analyze the eligibility, completeness, and usefulness of student worksheets, and student learning activities using student worksheets. This research is a qualitative study through case and document studies. The results of the eligibility and completeness of student worksheet components were obtained based the eligibility and completeness questionnaire with the specified indicators. The results of the usefulness of student worksheet were obtained through student and teacher response questionnaires. The results of student learning activities were obtained through observations of student learning activities based on the Understanding by Design (UbD) approach. The results indicated that the eligibility of student worksheets was in the less eligible category with 50 score, the completeness of student worksheet components in the complete category with 80 score, the usefulness of student worksheets for students in the useful category with 67,77 score, the usefulness of student worksheets for teachers in the useful category with 78,55 score, and student learning activities using student worksheets in the inactive category with 5,84 score.